Socio Economic Impact of Water Crisis on Agrarian Community in District Faisalabad, Pakistan - Asim, Muhammad; Vains, Ali Hassan; Yousaf, Haroon; Ramzan, Muhammad Azam (Richtmann Publishing, 2012)
Agriculture plays a pivotal role in the national economy of Pakistan. 65% of total population of Pakistan is living invillages and their major source of livelihood depends upon agriculture. Pakistan has the largest world irrigation system itsirrigation strength three times more than that of Russia. But unfortunately, Pakistani farmers are facing serious water shortageproblem in these days. The main objectives of the present study were to explore the effects of scarcity of canal water on theyield of different type of major crops and assess the affect of ground water on crops and its socio economic implication on thefarmers’ lives. A sample of 160 household farmers was selected through multistage sampling techniques. Specifically throughthis study, farmers’ survival due to the shortage of irrigation water highly depends upon tube well water. Due to this phenomenonnot only farmers have to pay lot of money in the form of fuel but also tube well water negatively affects the crops yield. Theresearchers also found out the socio economic problems due to the water crises such as irrigation water disputes, lesscultivation, lack of interest of livestock and these notions also badly affect their crops yield as well as their socio economiccondition.